CrowdRec: Um protótipo de sistema de recomendação para plataformas de crowdsourcing utilizando Google Venture Design Sprint - Ferreira, Tiago Moraes; Costella, Fernando Luiz; Zanetti, Alisson Borges; da Silva, Silvano Elias; Zanatta, Alexandre Lazaretti; De Marchi, Ana Carolina Bertoletti (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2019: Anais do XV Simpósio Brasileiro de Sistemas de Informação, 2019)
Collective intelligence is an interdisciplinary topic that has been explored by different areas of knowledge, like information systems, being a common practice of knowledge exchange through new forms of organization and flexible coordination in real time. Crowdsourcing emerges in this context as an act of externalizing, through the Internet, a task traditionally done internally in the organization for an undefined (and often large) group of people. However, one of the challenges found in this model is how users select and interact with available tasks for execution. Therefore, this work presents a prototype task recommendation system tool, with user experience-oriented design (UX), called CrowdRec, executed through the Google Ventures Design Studio method in conjunction with the Quant-UX tool. To evaluate the results, the TAM analysis with a five-point Likert scale was used. The results show positive interactions in the prototype.